Development and validation of the Axiom®Apple480K SNP genotyping array. (April 2016) - Bianco, Luca; Cestaro, Alessandro; Linsmith, Gareth; Muranty, Hélène; Denancé, Caroline; Théron, Anthony; Poncet, Charles; Micheletti, Diego; Kerschbamer, Emanuela; Di Pierro, Erica A.; Larger, Simone; Pindo, Massimo; et al.
Summary: Cultivated apple ( Malus  ×  domestica Borkh.) is one of the most important fruit crops in temperate regions, and has great economic and cultural value. The apple genome is highly heterozygous and has undergone a recent duplication which, combined with a rapid linkage disequilibrium decay, makes it difficult to perform genome‐wide association (GWA) studies. Single nucleotide polymorphism arrays offer highly multiplexed assays at a relatively low cost per data point and can be a valid tool for the identification of the markers associated with traits of interest. Here, we describe the development and validation of a 487K SNP Affymetrix Axiom ® genotyping array for apple and discuss its potential applications. The array has been built from the high‐depth resequencing of 63 different cultivars covering most of the genetic diversity in cultivated apple. The SNPs were chosen by applying a focal points approach to enrich genic regions, but also to reach a uniform coverage of non‐genic regions. A total of 1324 apple accessions, including the 92 progenies of two mapping populations, have been genotyped with the Axiom ® Apple480K to assess the effectiveness of the array. A large majority of SNPs (359 994 or 74%) fell in the stringent class of poly high resolution polymorphisms. We also devised a filtering procedure to identify a subset of 275K very robust markers that can be safely used for germplasm surveys in apple. The Axiom ® Apple480K has now been commercially released both for public and proprietary use and will likely be a reference tool for GWA studies in apple. Significance Statement: Single nucleotide polymorphism (SNP) array‐based genotyping has revolutionized the study of genome‐wide genetic variation. Here we describe a SNP array for cultivated apple, developed from 63 apple cultivars, with more than 487K SNPs well distributed among the 17 chromosomes. We describe the filtering pipeline and validate a large subset of highly reliable markers that can be used for germplasm surveys.